Analisis Pengaruh Zakat dan Infak Terhadap Tingkat Kedalaman Kemiskinan, Keparahan Kemiskinan dan Gini Rasio di Indonesia Tahun 2007-2018 - Aminullah Achmad Muttaqin; Anis Safitri (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2020)
Poverty in Indonesia has decreased in recent years, though slowing. Besides that, zakat and infaq have increased from year to year. Based on this phenomenon, this study aims to determine the effect of zakat and infaq on poverty and income disparities in Indonesia. The method used is a quantitative approach with descriptive and inferential analysis (multiple linear regression analysis). The data used are secondary data with zakat, infaq, poverty gap index, poverty severity index, and gini coefficient (gini ratio). The results of T test and F test shows the value of sig. 0,00 less than 0,05. Overall, zakat and infaq have a significant effect on the poverty gap, poverty severity and gini ratio. While partially, zakat and infaq also have a significant effect on the poverty gap, poverty severity and gini ratio. Zakat has a negative relationship to the poverty gap and poverty severity, while infaq has a negative relationship to the gini ratio.